Gingival crevicular fluid oxidative stress level in patients with periodontal disease and hyperlipidemia - Müge Lutfioğlu; Ahmet Aydoğdu; Vadim Ekrem Atabay; Elif Eser Sakallioğlu; Bahattin Avci (Sociedade Brasileira de Pesquisa Odontológica, 2017)
Abstract: This study aimed to assess the impact of hyperlipidemia on healthy and diseased periodontal tissue by evaluating oxidative stress biomarkers in gingival crevicular fluid (GCF). Clinical periodontal parameters and blood serum lipid, GCF malondialdehyde (MDA), protein carbonyl (PC), and total antioxidant capacity (TAOC) levels were evaluated in six age and sex-matched groups (n = 15 each) of normolipidemic and hyperlipidemic individuals as follows: normolipidemic + periodontally healthy (H), normolipidemic + gingivitis (G), normolipidemic + chronic periodontitis (CP), hyperlipidemic + periodontally healthy (HH), hyperlipidemic + gingivitis (HG), and hyperlipidemic + CP (HCP). GCF MDA, and PC levels varied among groups, with patients with periodontitis having the highest MDA and PC levels [CP > G > H (p < 0.01) and HCP > HG > HH (p < 0.01)] and the lowest TAOC levels [CP < G < H (p < 0.01) and HCP < HG < HH (p < 0.01)]. Furthermore, paired comparisons showed MDA and PC levels to be higher and TAOC levels to be lower in HCP compared with NCP (p < 0.01). In patients with hyperlipidemia, GCF, MDA, and PC levels positively correlated with clinical assessments and serum triglycerides (TG), total cholesterol (TC), and low-density lipoprotein cholesterol (LDL) levels and negatively correlated with serum high-density lipoprotein cholesterol (HDL) levels, whereas GCF TAOC levels negatively correlated with clinical assessments and serum TG, TC, and LDL levels, but positively correlated with serum HDL levels (p < 0.01). In normolipidemic patients, GCF, MDA, and PC levels positively correlated with clinical assessments and serum TG levels and negatively correlated with serum HDL levels, whereas GCF TAOC levels negatively correlated with clinical assessments and serum TG levels and positively correlated with serum HDL levels (p < 0.01). In conclusion, abnormal serum lipid subfractions could be considered a risk factor for enhancing oxidative stress in GCF in the presence of periodontal disease.